До питання про визначення терміну "інженерно-технічна інтелігенція" - Коротяєв, С.І. (Історичний архів. Наукові студії, 2014)
Розглянуто застосування терміну «інженерно-технічна інтелігенція» в
історіографії, виявлено критерії приналежності до соціально-професійної групи, яка
визначається цим терміном, дано його визначення. Рассмотрено применение термина «инженерно-техническая интеллигенция» в
историографии, выявлено критерии принадлежности к социально-профессиональной
группе, обозначаемой данным термином, дано его определение. The usage of the term «engineering and technical intelligentsia» in the historiography of our
country is considered, the criteria for belonging to the socio-professional group, designated by
this term, are revealed, its definition is given.
A person is an element of any form of the social phenomenon, from the simplest
communities to modern civilization’s and political supersystems. That’s why the view on the
historical processes and on the society is not isolated from the study of separate strata. It is
spoken about engineering and technical intelligentsia, peculiarities of its existence, sources of
its formation.